Effect of the volume fraction of zirconia suspensions on the microstructure and physical properties of products produced by additive manufacturing. Issue 5 (May 2019) - Jang, Kyoung-Jun; Kang, Jin-Ho; Fisher, John G.; Park, Sang-Won
Highlights: Zirconia products printed by additive manufacturing using zirconia suspensions. Sintered specimens using zirconia suspensions had inferior physical properties. Light scattering makes some distortion and cause geometrical overgrowth. Future challenges include increasing precision and bending strength. Abstract: Objective: The objectives of the present study were: (1) to analyze the dispersion and optical properties of suspensions with various volume fractions of zirconia, and (2) to assess the influence of zirconia volume fraction on the microstructure and physical properties of products produced by the additive manufacturing and sintering process. Methods: Zirconia specimens were fabricated by an additive manufacturing technique using a DLP (digital light processing) system. The zirconia suspensions were divided into six groups based on zirconia volume fraction within the range of 48–58 vol%. Results: The maximum volume fraction of zirconia in suspensions possible for printing was 58 vol%. The cure depth of the zirconia suspensions decreased as the volume fraction increased. The cure depth was greater than 100 μm after 15 s photocuring in all groups. Geometrical overgrowth tended to increase gradually as the volume fraction of zirconia increased within the range of 28.55–36.94%. The 3-point bending strength of the specimens increased as the volume fraction of zirconia in the suspension increased, reaching a maximum value of 674.74 ± 32.35 MPa for a volume fraction of 58 vol%. Cracks were observed on the surfaces of zirconia specimens and these cracks increased in number as zirconia volume fraction decreased. Significance: In this experiment, the viscosity of zirconia suspensions sharply increased from a volume fraction of 54 vol%. Because of the very high viscosity, 58 vol% was the maximum volume fraction possible for additive manufacturing. After polymerization, all specimens showed some distortion due to geometrical overgrowth. The maximum 3-point bending strength was 674.74 ± 32.35 MPa for a volume fraction of 58 vol%. But the maximum strength of sintered zirconia prepared by additive manufacturing is inferior to that of conventionally sintered zirconia.